Comparing efficacy cognitive behavioral therapy & motivational interviewing on adherence to treatment in elderly with diabetes living in nursing homes and living at home - Mahsa Hadizadeh; javad khalatbari; Hasan Ahadi (مجله علوم روانشناختی)
Background: inability to adherence treatment is a general and special health problem in the treatment of elderly people with diabetes. therapies Studies have reported on the effect of cognitive behavioral therapy to improvement adherence to treatment, also, motivational interviewing by empowering effect on this behavior. However, compares the effect these in elderly people with diabetes has been overlooked. Aims: the aim of this study to compare the efficacy of cognitive behavioral therapy & motivational interviewing on adherence to treatment in elderly people with diabetes living in nursing homes and living at home. Methods: Research method was quasi-experimental with pre-test, post- test with control group. The statistical population consist of all elderly diabetics were living at home and living in nursing homes in Tehran in 1400. Sampling method was Convenience Sampling. 75 people were selected and replaced in 5 groups of 15 people (60 people in 4 experimental groups and 15 people in a control group). Research tools include; The Adherence to treatment questionnaire Seyed Fatemi (1970), cognitive behavioral therapy protocols (Younk et al., 2011) and motivational interview by Miller and Rolink (2019). The data were analyzed using the statistical test of Analysis of covariance with repeated measures and Benferroni test. Results: The results showed that the two intervention methods of cognitive behavioral therapy and motivational interview had a significant effect on adherence to treatment scores in the post-test. The effect of the group was different according to the measurement time levels. The experimental intervention led to changes in the experimental group, which was 0.47 of the total changes caused by the experimental procedure (p< 0.01). Considering that the average of the motivational interview group was higher than the cognitive behavioral therapy, then motivational interviewing was more effective in increasing the adherence to treatment of elderly people with diabetes living in nursing homes and living at home. Conclusion: Both cognitive behavioral therapy and motivational interviewing can improve adherence to treatment in nursing home and home-dwelling elderly with diabetes. The mentioned findings can help therapists to choose the type of treatment.